First report of Panicum repens L., as a potential weed in Costa Rica. - Retana-Sánchez, Kenneth (2013)
The objective of this work was to provide information on Panicum repens as a potential weed in Costa Rica, and the taxonomy associated with this specie for its correct identification. In April 2012, the first weed samples of an unidentified grass species was received at the Weed Science Laboratory of the University of Costa Rica and EARTH University; the sample was collected at a roadside in front of a cattle farm in San Carlos, Alajuela, Costa Rica. Once the taxonomic details on the spikelets and root system were analyzed, the species was identified as Panicum repens L., which was not yet reported at national herbariums (National Herbarium, and Biology School of the University of Costa Rica) or in specialized literature of the subject. Taxonomic characteristics for the identification of Panicum repens are included for its identification.